Determinan Profitabilitas Bank Umum Syariah di Indonesia - Uun Sunarsih; Siti Aisah Rahmah Wati (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to examine the effect of leverage, liquidity, and firm size on profitability. The population in this study is Islamic Commercial Banks (BUS) registered with the Financial Services Authority for the period 2017-2020 using purposive sampling and obtained 12 Islamic Commercial Banks. The data in this study are secondary data obtained through www.ojk.go.id. The results showed that leverage had a positive effect on profitability. This shows that leverage affects management performance in managing funds so that it can increase profitability. So the more debt used, the BUS will be encouraged to increase its profitability. Liquidity has no effect on profitability, this is because the level of the company's ability to pay its short-term debt does not affect the size of the profitability of the BUS. The size of the company affects profitability, this is because large companies get more pressure from investors so that more investors invest, it can increase profitability.